Adherence to nutritional recommendations and sociodemographic variables in patients with diabetes mellitus - Maria Lucia Zanetti; Clarissa Cordeiro Alves Arrelias; Rosana Cristina Franco; Manoel Antônio dos Santos; Flávia Fernanda Luchetti Rodrigues; Heloisa Turcatto Gimenes Faria (SciELO, 2015)
OBJECTIVETo determine if there is a relationship between adherence to nutritional recommendations and sociodemographic variables in Brazilian patients with type 2 diabetes mellitus.METHODSCross-sectional observational study using a stratified random sample of 423 individuals. The Food Frequency Questionnaire (FFQ) was used, and the Fisher's exact test was applied with 95% confidence interval (p<0.05).RESULTSOf the 423 subjects, 66.7% were women, mean age of 62.4 years (SD = 11.8), 4.3 years of schooling on average (SD = 3.6) and family income of less than two minimum wages. There was association between the female gender and adherence to diet with adequate cholesterol content (OR: 2.03; CI: 1.23; 3.34), between four and more years of education and adherence to fractionation of meals (OR: 1 92 CI: 1.19; 3.10), and income of less than two minimum wages and adherence to diet with adequate cholesterol content (OR: 1.74; CI: 1.03, 2.95).CONCLUSIONAdherence to nutritional recommendations was associated with the female gender, more than four years of education and family income of less than two minimum wages.